The Luhmannian approach to exclusion/inclusion and its relevance to Social Work1. (January 2015) - Schirmer, Werner; Michailakis, Dimitris
Summary: Although the concept of social exclusion is central to the academic discipline of social work, there is not much theoretical clarity about what it actually means. For instance, exclusion is used as a synonym for poverty, marginalization, detachment, unemployment, or solitude. We argue that the systems-theoretical framework developed by the German social theorist Niklas Luhmann (1927–1997) provides the conceptual tools to understand inclusion and exclusion in a theoretically adequate way that is highly relevant to Social Work. Since there is scarcely any literature on Luhmann's work in the field of social work not written in German, this article aims to provide a systematic introduction to the Luhmannian theory of society with respect to the distinction of inclusion/exclusion and its relation to social work to an English-speaking audience . Findings: After a presentation of some basic concepts, it will be argued that exclusion is not a problem per se nor is inclusion always and per se unproblematic. The Luhmannian approach suggests that inclusion and exclusion are operations of social systems that treat human beings as relevant addresses for communication. Against that background, systems theory gives a clear and accurate description of what social work can (and cannot) do in terms of inclusion/exclusion. Applications: The main purpose of social work is exclusion management. Exclusion management involves working on the social addresses of individuals with the aim of improving their attractiveness for other social systems, a (re)orientation towards being includable. It appears in three forms: exclusion prevention, inclusion mediation, and exclusion administration.